A study of youth perception towards retirement planning in Malaysia - Leong, Pik Lin (2019)
The quantities of elderly individuals in Malaysia is increasing fast. The wellbeing status of the elderly has improved gradually since 1982, resulting elderly individuals living longer self-reliantly. Growing long life, a decreasing birth rate, and the maturing of the large cohort of baby boomers have all added to this upsurge. Slow economic growth, a change from trades in the industrial sector to the service sector, shifting pension plans, and reducing employer paternalism all may affect retirement planning. The essential to begin searching for a national strategy to help Malaysians in improving their personal financial literacy and build up the important skills to keep their personal financial healthier in the proper perspective is vital. Approaches to inspire and improve financial literacy among Malaysian should focus on financial activities, skills, knowledge and behaviour. The plans could help individual’s capacity and ability in a better placed to contribute towards individual’s financial wellbeing and stronger development in the marketplace. Therefore, this study tends to examine the factors affecting youth perception towards retirement planning. Seven independent variables are being adapted and adopted in this research to identify the major factors which includes awareness about retirement planning, saving behaviour, social security, financial literacy, attitudes towards investment, social influences and trust. A total of 343 respondents from Greater KL area were participated and responded in this survey. Based on the findings and analysis, this study revealed that the parents play a vital role to improve the awareness about retirement planning among youth. The outcomes would be useful to policy maker and financial advisors as good reference to improve the retirement planning awareness among youth and so enhance the economic growth. Lastly, based on the findings, the researcher also suggested a few proposals for further study and improvement.